Grassroots Women's Leadership in the Family Hope Program as Part of Sustainable Development: A Case Study in a Border Regency - Beni, Sabinus; Atlantika, Yeremia Niaga; Salfarini, Eligia Monixa; Vuspitasari, Benedhikta Kikky (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
The Family Hope Program (PKH) is a cornerstone of Indonesia’s poverty reduction strategy, yet its success at the local level often depends on informal leadership. This study examines the role of grassroots women’s leadership in PKH implementation in Lumar District, Bengkayang Regency, West Kalimantan. While existing literature often views women solely as program beneficiaries, this research addresses a gap by analyzing women as active informal leaders who mediate policy and community participation in border regions. Using a qualitative case study approach, data were collected through in-depth interviews with 12 participants (including PKH coordinators and group leaders), participant observation in Family Capacity Building Meetings (P2K2), and document analysis. The data were analyzed using thematic analysis. Findings reveal that grassroots women perform four critical roles: socialization, mentoring, group organization, and advocacy. Their leadership is a primary driver for achieving Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) and SDG 5 (Gender Equality). The study concludes that strengthening the informal leadership capacity of women is essential for the sustainability of social protection programs in remote areas.